Comparing the Effectiveness of Betamethasone Gel with Lidocaine Gel Application on Endotracheal Tube in Preventing Post Operating Sore Throat - Hira Asad, Hamid Mehmood, Shahid Hussain, Rashid Hussain, Muhammad Arshed, Imran Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the effectiveness of betamethasone gel and lidocaine gel application in reduction of post-operative sore throat. Study Design: Randomized controlled trial Place and Duration: Study was conducted at anesthesia department of Dow University of Health Sciences, Karachi with duration from May 2022 to October 2022. Methodology: A total of 54 patients were enrolled and divided into two groups Betamethasone and Lidocaine (Lignocaine) by lottery method. In one group betamethasone gel 0.05% was applied over endotracheal tube (ETT) and in other group lignocaine gel 4% was applied over the ETTT. SPSS version 23 was used for data analysis. Mean ± SD and frequency (percentage) were calculated for numerical and categorical data respectively. Results: Majority of the patients in betamethasone group, 15 (55.6%) patients, had not developed sore throat whereas mild and moderate sore throat was most common in lidocaine group. Further, 5 (18.5%) patients in lidocaine group and only 2 (7.4%) patients in betamethasone group was severe sore throat. (p=0.015). Practical implication: Sore throat is a common post-operative complication having potential to lead poor surgical results. This study will help the clinicians/anesthesiologists to overcome the problem and reduce the incidence of sore throat in routine practice. Conclusion: Application of betamethasone gel over endotracheal tube just before insertion is associated with reduced risk of sore throat as compare to lignocaine gel. Keywords: Lidocaine gel, Betamethasone gel, Post-operative sore throat, Laryngoscopy, Endotracheal tube.